In vitro evaluation of papaverine hydrochloride incompatibilities: a simulation of intraarterial infusion for cerebral vasospasm. - Mathis, J M; DeNardo, A J; Thibault, L; Jensen, M E; Savory, J; Dion, J E (American Journal of Neuroradiology, 1994)
PURPOSE To elucidate, in light of reports of complications associated with intraarterial infusion of papaverine hydrochloride, the known propensity of papaverine hydrochloride to form precipitate in combination with other solutions or pharmaceuticals. METHODS Initially simulating a situation experienced during an intraarterial papaverine infusion for cerebral vasospasm, we mixed various concentrations of papaverine with serum, nonheparinized and heparinized saline, and nonionic contrast material. RESULTS Papaverine in concentrations of 0.3% (300 mg/100 mL of normal saline) or greater formed a precipitate when mixed with human serum (blood). The precipitate crystals were 50 to 100 microns in size and could be returned to solution simply by the addition of more serum. CONCLUSION Crystal emboli are a possible transient cause of complications experienced during treatment of vasospasm with its attendant altered flow dynamics.